2016
DOI: 10.1039/c6em00416d
|View full text |Cite
|
Sign up to set email alerts
|

Source contributions and potential source regions of size-resolved water-soluble organic carbon measured at an urban site over one year

Abstract: In this study, 24 h size-segregated particulate matter (PM) samples were collected between September 2012 and August 2013 at an urban site in Korea to investigate seasonal mass size distributions of PM and its water-soluble components as well as to infer the possible sources of size-resolved water-soluble organic carbon (WSOC) using a positive matrix factorization (PMF) model. The potential source contribution function (PSCF) was also computed to identify the possible source regions of size-resolved WSOC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…) under typical ambient conditions at an urban site showed dominant droplet modes peaking at 0.55 m [2,38,39]. Meanwhile particle size distributions at the urban site during the haze event with air stagnation, high RH, and regional transportation, in the fall season, exhibited dominant droplet modes at a particle size of 1.0 m [3].…”
Section: -mentioning
confidence: 91%
See 4 more Smart Citations
“…) under typical ambient conditions at an urban site showed dominant droplet modes peaking at 0.55 m [2,38,39]. Meanwhile particle size distributions at the urban site during the haze event with air stagnation, high RH, and regional transportation, in the fall season, exhibited dominant droplet modes at a particle size of 1.0 m [3].…”
Section: -mentioning
confidence: 91%
“…Meanwhile particle size distributions at the urban site during the haze event with air stagnation, high RH, and regional transportation, in the fall season, exhibited dominant droplet modes at a particle size of 1.0 m [3]. Yu et al [2] also conducted a source apportionment of size-resolved WSOC for one year at an urban site. In their study, condensation mode WSOC was found to be strongly associated with secondary organic aerosols and biomass burning (BB) emissions, while heterogeneous reactions and long-range transports were found to be important contributors to the droplet mode WSOC formation.…”
Section: -mentioning
confidence: 99%
See 3 more Smart Citations